Benefits of non-work interactions with your supervisor: Exploring the bottom-up effect of employee boundary blurring behavior on abusive supervision - Jiang, Luyuan; He, Guohua; Zhou, Hansen; Yang, Laijie; Li, Xiaolan; Li, Wenpu; Qin, Xin (Frontiers in Psychology, 2022)
Abusive supervision has long been found to have remarkably negative impacts on individual and organizational outcomes. Accordingly, prior studies have explored many organizational and supervisory predictors of abusive supervision and offered several interventions to reduce it. However, extant research lacks the bottom-up perspective to explore how employees can act to reduce abusive supervision, which is an important factor that enriches abusive supervision literature and helps employees protect themselves from being abused. Drawing on self-disclosure theory, we develop a model of whether and how employee boundary blurring behavior may protect them from being abused by their supervisors. Specifically, we conducted two studies to test the theoretical model, including a scenario-based experimental study and a multi-source, multi-wave field study. The results reveal a negative indirect effect of employee boundary blurring behavior on abusive supervision via supervisor liking toward the employee. By uncovering employee boundary blurring behavior as an antecedent of abusive supervision, we enrich the abusive supervision literature with a bottom-up behavioral strategy for employees to proactively protect themselves from being abused. We hope our findings will encourage future studies to identify boundary conditions and other solutions for employees to minimize the risk of being abused.